OPTIMALISASI BIAYA MINIMUM DALAM PEMENUHAN ASUPAN KEBUTUHAN GIZI MAKANAN ANAK USIA SEKOLAH DENGAN METODE SIMPLEKS - Aden Aden; Ilmadi Ilmadi; Eka Febriani (Prodi Matematika FMIPA Unirow Tuban, 2022)
School-age children are the initial capital of a country because they are the next generation who will determine the quality of the country in the future. At school age children, a balanced nutritional intake in their diet must be fulfilled because it greatly affects the cognitive growth of children because school age children are still vulnerable to nutritional problems. Parents' low knowledge of nutrition is accompanied by a low economic level, which has an impact on limited costs to meet the balanced nutrition of their children. In this study, a minimum cost optimization model will be formed to fulfill the nutritional intake of food for children in accordance with the standard Nutritional Adequacy Ratio (RDA) using the simplex method with the help of the POM-QM application. The results of the study obtained the form of the optimization model, namely, Z = which was obtained on the fifth combination menu. The optimal combination of food ingredients is which is 210.2327 grams of rice, is 569.4991 grams of cassava leaves, is 0 grams of tempeh, is 128.6347 catfish, is 45.8144 papayas. grams and which is 0 grams of milk. With a minimum fee of IDR 9,335.685, rounded up to IDR 9,300 per day.